Między "Diariuszem" Prokopa Zbigniewskiego a "Chorągwią sauromatcką" Marcina Paszkowskiego - pamiętnikarski wzorzec prozą i?jego wierszowane powielenie propagandowe = Prokop Zbigniewski`s "Diary" and Marcin Paszkowski`s "Chorągiew sauromatcka" - prosed diary original and its poematic duplication - Sznajder, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study refers to a problem of confusing similarity between two XVII centuary literary worksconcerning the Battle of Khotyn (1621), i.e. "Chorągiew sauromatcka" written by Marcin Paszkowskiand Prokop Zbigniewski`s "Diariusz". The poet of the House of Zadora used to plagiarized in most ofhis early writings which was quickly proven in professional literature. A question arisen whetherPaszkowski did also plagiarize in his latest known work or did he wrote it all by himself?
Keywords: Zbigniewski, Prokop; Paszkowski, Marcin - twórczość; pamiętnikarstwo polskie; literatura polska - historia - 10-16 w.